Advanced hepatocellular carcinoma with response to lenvatinib after atezolizumab plus bevacizumab. Issue 42 (22nd October 2021) - Yano, Shigeki; Kawaoka, Tomokazu; Johira, Yusuke; Miura, Ryoichi; Kosaka, Masanari; Shirane, Yuki; Murakami, Serami; Amioka, Kei; Naruto, Kensuke; Ando, Yuwa; Kosaka, Yumi; Yamaoka, Kenji; et al.
Abstract: Rationale: Various treatments are available for treating hepatocellular carcinoma (HCC). The immune checkpoint inhibitor combination of atezolizumab plus bevacizumab was recently approved for the treatment of unresectable HCC, but there are few reports on the failure of the combination treatment. Here, we present a case of unresectable HCC with adrenal metastasis that was eventually operated on after lenvatinib (LEN) treatment that followed failed treatment with atezolizumab plus bevacizumab. Patient concerns: A 68-year-old man was diagnosed with non-alcoholic steatohepatitis-based HCC with adrenal metastasis. Diagnosis: Cirrhosis was classified as Child-Pugh score of 5. HCC was diagnosed as Barcelona Clinic Liver Cancer stage C. Interventions: We initiated treatment with atezolizumab plus bevacizumab. Liver dysfunction appeared 2 days after the first administration but was improved by intravenous rehydration and did not appear after the second course. The HCC shrank, but the adrenal metastasis grew bigger after the fourth course, so we changed the therapy to LEN. After HCC and adrenal metastasis were necrotic by LEN, conversion surgery was performed. Outcomes: After successful conversion therapy, the general condition of the patient was good, and has been carefully followed for 4 months to date without any evidence of further recurrences. Lessons: This case showed that even if atezolizumab plus bevacizumab is not effective, multidisciplinary treatment such as LEN and conversion surgery is possible. Given the efficacy of LEN after atezolizumab plus bevacizumab, it is important to consider that there is a possibility of cure even when first-line treatment is not effective for a patient with unresectable HCC.